Longitudinal Radiological Findings in Patients With COVID-19 With Different Severities: From Onset to Long-Term Follow-Up After Discharge - Zhao, Yajing; Wang, Dongdong; Mei, Nan; Yin, Bo; Li, Xuanxuan; Zheng, Yingyan; Xiao, Anling; Yu, Xiangrong; Qiu, Xiaohui; Lu, Yiping; Liu, Li (Frontiers in Medicine, 2021)
Objective: To investigate the evolution of radiological findings in COVID-19 pneumonia patients with different severities from onset to 1-year follow-up and identify predictive factors for different pulmonary lesion absorption status in COVID-19 patients. Methods: A retrospective study was performed on the clinical and radiological features of 175 COVID-19 pneumonia patients hospitalized at three institutions. All chest CT scans during hospitalization and follow-ups after discharge were collected. The clinical and radiological features from chest CT scans both at the peak stage and before discharge, were used to predict whether the pulmonary lesions would be fully absorbed after discharge by Cox regression. Then, these patients were stratified into two groups with different risks of pulmonary lesion absorption and an optimal timepoint for the first CT follow-up was selected accordingly. Results: 132 patients were classified into the non-severe group, and 43 patients were classified into the severe group according to WHO guidelines. The opacification in both groups changed from ground-glass opacity (GGO) to consolidation and then from consolidation to GGO. Among the 175 participants, 135 underwent follow-up CT scans after discharge. Pulmonary residuals could be observed in nearly half of the patients with the presentation of opacities and parenchymal bands. The parenchymal bands in nine discharged patients got fully absorbed during follow-up periods. Patient`s age, level of LDH, level of procalcitonin, existence of diffuse lesions, subpleural distribution of lesions, morphology of residuals and pleural traction from the last scan before discharge were independent factors to predict the absorption status of COVID-19-related pulmonary abnormalities after discharge. According to Kaplan-Meier analysis, the probability of patients of the low-risk group to have pulmonary lesions fully absorbed within 90 days reached 91.7%. Conclusion: The development of COVID-19 lesions followed the trend from GGO to consolidation and then from consolidation to GGO. The CT manifestations and clinical and laboratory variables before discharge could help predict the absorption status of pulmonary lesions after discharge. The parenchymal bands could be fully absorbed in some COVID-19 cases. Our Cox regression analysis indicated that the timepoint of 3 months since onset as optimal for the radiological follow-up of discharged patients.